Efektifitas terapi musik mozart terhadap penurunan Intensitas nyeri pada pasien post operasi Fraktur ekstremitas bawah - Muhammad - Firdaus; Bayhakky - -; Misrawati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this study was to determine the effectiveness of Mozart music therapy to reduce pain in post surgery patients of lower extremity fracture. This study used quasy experiment with pretest-posttest design with control group approach. Purposive sampling technique with inclusion criteria was used to recruit 30 respondents. The instrument in this study was observational sheet with pain scale with 1-10 score. The data were analyzed by using paired sample t-test and independent sample t-test. The result showed p value 0,000. It meant there was a differences between experimental group and control group.  This result showed that distraction technique which listening Mozart Music therapy was effective to reduce pain. Based on this result, it is recommended to health provider especially nurses to use Mozart Music therapy as one of non pharmacological therapy to reduce pain. Keywords : Fracture, Mozart music, pain